SPIRITUAL BASIS AND FACTORS IN THE EMERGENCE OF MYSTICISM (QUR'AN ON THE BASIS OF KARIM VERSES AND HADITH SHARIF PROVERBS) - Saidakbarova Muqaddas Muhammadrahimovna; Zohidova Durdona Lutfullayevna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In the article, the emergence of the doctrine of Sufism, the basis and factors that it is a doctrine that grew out of the Holy Qur'an and hadith, the period of asceticism of the doctrine of Sufism, the three stages of asceticism, attitude to asceticism and piety, asceticism and mysticism, the three stages of asceticism Scientific and theoretical information is provided about the career of Rabiyya al-Adawiyah and the emergence of Sufism literature.